Transparency in Healthcare Reporting: The Case of External Contractors and Consultants in New Zealand’s Healthcare System - Adeel Akmal; Robin Gauld; Erin Penno (International Journal of Health Policy and Management, 2022)
This study investigates the quality of reporting around the spending related to the use of external consultant and contractors in New Zealand’s 20 District Health Boards (DHBs). We make use of the publicly available annual reviews conducted by the New Zealand Parliament Health Select Committee (HSC) as well as DHB data which were retrieved using Official Information Act (OIA) requests. The quality of reporting was judged on the differences and discrepancies observed in the HSC reports each year as well as the DHB internal data. Perhaps, unsurprisingly, total spending on external consultants and contractors has been increasing over the years while the quality of reporting has been decreasing. Our analysis highlighted a number of quality issues—mistakes, discrepancies and an overall lack of standardised reporting in almost all of the DHBs. Some of these discrepancies included failure to provide information required by the HSC, differences in yearly total amounts in consecutive reports and differences between information provided to the HSC and to the authors of this article. It is hoped that this research and the prospective areas for improvement highlighted here are used as a guide to improve the quality of healthcare financial reporting.